2021
DOI: 10.18280/ijht.390324
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Non-Newtonian Model on Properties of Blood Flow Through a Left Coronary Artery with Presence of Different Double Stenosis

Abstract: Cardiovascular diseases were the main cause for loosing lives in the last decades due to the restricted blood flow states in the blood vessels areas. Numerical investigations have been conducted as the aim of this work to examine the blood flow, and wall shear stresses adjacent to the mono stenosis up to different degrees involved in the main, side and distal main branches as well as observe the pulsatile flow of blood in the left coronary artery through various percentage of stenosis. Both the Carreau non-New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The transient blood flow across a stenosed artery is examined by Hisham et al 11 Kadhim et al studied the influence of non-Newtonian model on properties of blood flow through a left coronary artery with presence of different double stenosis. 12 Jamil et al described the effects of magnetic Casson blood flow in an inclined multi-stenosed artery by using Caputo-Fabrizio fractional derivative. 13 The nanofluid is the kind of fluids that consists of nanometer sized particles (known as nanoparticle) in the base fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The transient blood flow across a stenosed artery is examined by Hisham et al 11 Kadhim et al studied the influence of non-Newtonian model on properties of blood flow through a left coronary artery with presence of different double stenosis. 12 Jamil et al described the effects of magnetic Casson blood flow in an inclined multi-stenosed artery by using Caputo-Fabrizio fractional derivative. 13 The nanofluid is the kind of fluids that consists of nanometer sized particles (known as nanoparticle) in the base fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The already available research work clearly reveals that there is not a single research article that provides the hemodynamics mechanism of a curved artery having multiple stenosis. Some recent research articles relevant to the context are [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Reddy et al [11] reported the influence of viscosity on Jeffrey fluid peristaltic flow in a uniform tube. Kadhim et al [12] studied whether the blood flow in the arterial area was within the range of possible non-Newtonian rheological qualities in the presence of various twofold stenosis in the left coronary artery. In another study, Hayat et al [13] explored the peristaltic flow in a tube with an endoscope.…”
Section: Introductionmentioning
confidence: 99%